Sociodemographic and Psychopathologic Predictors of First Incidence of DSM-IV Substance Use, Mood, and Anxiety Disorders: Results from the Wave 2 National Epidemiologic Survey on Alcohol and Related Conditions - Grant, Bridget F. (2008)
The objective of this study was to present nationally representative findings on sociodemographic and psychopathologic predictors of first incidence of DSM-IV substance, mood and anxiety disorders using the Wave 2 National Epidemiologic Survey on Alcohol and Related Conditions. One-year incidence rates of DSM-IV substance, mood and anxiety disorders were highest for alcohol abuse (1.02) alcohol dependence (1.70), major depressive disorder (MDD: 1.51) and generalized anxiety disorder (GAD: 1.12). Incidence rates were significantly greater (p < 0.01) among men for substance use disorders and greater among women for mood and anxiety disorders except bipolar disorder and social phobia. Age was inversely related to all disorders. Black individuals were at decreased risk of incident alcohol abuse and Hispanic individuals were at decreased risk of GAD. Anxiety disorders at baseline more often predicted incidence of other anxiety disorders than mood disorders. Reciprocal temporal relationships were found between alcohol abuse and dependence, MDD and GAD, and GAD and panic disorder. Borderline and schizotypal personality disorders predicted most incident disorders. Incidence rates of substance, mood and anxiety disorders were comparable to or greater than rates of lung cancer, stroke, and cardiovascular disease. The greater incidence of all disorders in the youngest cohort underscores the need for increased vigilance in identifying and treating these disorders among young adults. Strong common factors and unique factors appear to underlie associations between alcohol abuse and dependence, MDD and GAD, and GAD and panic disorder. The major results of this study are discussed with regard to prevention and treatment implications.